The influence of Osmunda regalis root extract on head and neck cancer cell proliferation, invasion and gene expression - Marianne Schmidt; Josef Skaf; Georgiana Gavril; Christine Polednik; Jeanette Roller; Michael Kessler; Ulrike Holzgrabe (BMC, 2017)
Abstract Background According to only a handful of historical sources, Osmunda regalis, the royal fern, has been used already in the middle age as an anti-cancer remedy. To examine this ancient cancer cure, an ethanolic extract of the roots was prepared and analysed in vitro on its effectiveness against head and neck cancer cell lines. Methods Proliferation inhibition was measured with the MTT assay. Invasion inhibition was tested in a spheroid-based 3-D migration assay on different extracellular matrix surfaces. Corresponding changes in gene expression were analysed by qRT-PCR array. Induction of apoptosis was measured by fluorescence activated cell sorting (FACS) with the Annexin V binding method. The plant extract was analysed by preliminary phytochemical tests, liquid chromatography/mass spectroscopy (LC-MS) and thin layer chromatography (TLC). Anti-angiogenetic activity was determined by the tube formation assay. Results O. regalis extract revealed a growth inhibiting effect on the head and neck carcinoma cell lines HLaC78 and FaDu. The toxic effect seems to be partially modulated by p-glycoprotein, as the MDR-1 expressing HLaC79-Tax cells were less sensitive. O. regalis extract inhibited the invasion of cell lines on diverse extracellular matrix substrates significantly. Especially the dispersion of the highly motile cell line HlaC78 on laminin was almost completely abrogated. Motility inhibition on laminin was accompanied by differential gene regulation of a variety of genes involved in cell adhesion and metastasis. Furthermore, O. regalis extract triggered apoptosis in HNSCC cell lines and inhibited tube formation of endothelial cells. Preliminary phytochemical analysis proved the presence of tannins, glycosides, steroids and saponins. Liquid chromatography/mass spectroscopy (LC-MS) revealed a major peak of an unknown substance with a molecular mass of 864.15 Da, comprising about 50% of the total extract. Thin layer chromatography identified ferulic acid to be present in the extract. Conclusion The presented results justify the use of royal fern extracts as an anti-cancer remedy in history and imply a further analysis of ingredients.